Development and efficiency of banking and economic growth in Central and Eastern Europe - ĆURAK, Marijana (Annals of Spiru Haret University. Economic Series, 2010)
In an endogenous growth framework, well developed and efficient financial system can promote economic growth. A number of empirical studies confirmed this hypothesis. Since the financial systems of transition countries are dominated by banks, in this paper we analyze the importance of banking industry for economic growth using methods of panel data analysis for 15 Central and Eastern European countries in the period from 1992 to 2006. Using variables that measure both quantitative and qualitative aspects of financial intermediation, our findings support the view that the effectiveness of banking industry is more important than its size per se for the economic growth in the Central and Eastern European countries.